The Transformation of Social Norms and Legal Adaptation in Responding to the Phenomenon of Digital Bullying Among Urban Adolescents - Sitompul, Abdul Romadon; Dalimunteh, Nur Amannah (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The transition of digital technology has altered the social norms of urban adolescents, generating an online culture that often validates digital bullying as part of everyday life. The present study aims to investigate the dynamics of shifting social norms among adolescents in digital spaces and to assess the Indonesian legal system's adaptive capacity in responding to the phenomenon of digital bullying. The qualitative exploratory case study employed a multipronged data collection strategy, comprising interviews, digital ethnography, and document analysis, in the large cities of Jakarta, Surabaya, and Bandung. The results indicate that adolescents are allowing permissive norms regarding verbal aggression in interactions through digital media. In contrast, the law is seen as reactive, not child-friendly, and not oriented toward education. Adolescents tend to have a general distrust of formal legal mechanisms. The study concludes that the law's effectiveness ultimately depends on its ability to adapt to evolving digital norms. The main contribution of this research is combining the legal sociology and digital culture perspectives to propose a legal policy that is contextual, participatory, and focused on educating adolescents and ensuring their social protection. In practical terms, the findings provide policy recommendations to strengthen digital literacy programs in schools, develop adolescent-friendly reporting mechanisms, and encourage cross-sectoral collaboration to prevent and address digital bullying effectively.